The Role of MSME Business Development Training on Increasing Business Performance of BMT Beringharjo Ponorogo Partners - Harahap, Soritua Ahmad Ramdani; Firmansah, Yayan; Maulana, Hartomi; Kurniawan, Dhika Amalia; Astuti, Rahma Yudi; Rusli, Lathiefa; Abidin, M. Zaenal; Muhtar, Ali (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This research aims to determine the role of MSME business development training on improving the business performance of BMT Beringharjo Ponorogo partners. Design/Methode/Approach : In this research and service, we use direct observation methods in the field and use training and mentoring methods for BMT Beringharjo Ponorogo partners. Research Finding : The result of carrying out this research and service is that the MSME partners of BMT Beringharjo are able to understand and implement the concepts of financial recording, marketing methods through normal means and digital marketing, warehousing operations and HR management within the scope of their respective MSMEs